Carbamazepine Increases the Risk of Sudden Cardiac Arrest by a Reduction of the Cardiac Sodium Current - Jia, Lixia; Eroglu, Talip E.; Wilders, Ronald; Verkerk, Arie O.; Tan, Hanno L. (Frontiers in Cell and Developmental Biology, 2022)
Aim: To assess the risk of sudden cardiac arrest (SCA) associated with the use of carbamazepine (CBZ) and establish the possible underlying cellular electrophysiological mechanisms. Methods: The SCA risk association with CBZ was studied in general population cohorts using a case–control design (n = 5,473 SCA cases, 21,866 non-SCA controls). Effects of 1–100 µM CBZ on action potentials (APs) and individual membrane currents were determined in isolated rabbit and human cardiomyocytes using the patch clamp technique. Results: CBZ use was associated with increased risk of SCA compared with no use (adjusted odds ratio 1.90 [95% confidence interval: 1.12–3.24]). CBZ reduced the AP upstroke velocity of rabbit and human cardiomyocytes, without prominent changes in other AP parameters. The reduction occurred at ≥30 µM and was frequency-dependent with a more pronounced reduction at high stimulus frequencies. The cardiac sodium current (INa) was reduced at ≥30 µM; this was accompanied by a hyperpolarizing shift in the voltage-dependency of inactivation. The recovery from inactivation was slower, which is consistent with the more pronounced AP upstroke velocity reduction at high stimulus frequencies. The main cardiac K+ and Ca2+ currents were unaffected, except reduction of L type Ca2+ current by 100 µM CBZ. Conclusion: CBZ use is associated with an increased risk of SCA in the general population. At concentrations of 30 µM and above, CBZ reduces AP upstroke velocity and INa in cardiomyocytes. Since the concentration of 30 µM is well within the therapeutic range (20–40 µM), we conclude that CBZ increases the risk of SCA by a reduction of the cardiac INa.